FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KETERLAMBATAN PELAKSANAAN PEKERJAAN PENINGKATAN/PELEBARANJALAN GONDORUSO-JUGOSARI KECAMATAN PASIRIAN KABUPATEN LUMAJANG (Jurnal Spesialis Teknik Sipil (JSpTS), 2022)
Implementation of a project is very rarely encountered a project that runs exactly as planned. Project delays are often a source of disputes and claims between the owner and the contractor, so the value will be very expensive in terms of both the contractor and the owner. In general, project delays often occur due to changes in planning during the implementation process, poor managerial and contracting organizations, work plans that are not well managed and integrated, drawings and specifications are incomplete, or the contractor's failure to carry out the work. This study aims to determine the factors that influence the delay in the implementation of the work on the improvement / widening of the gondoruso-jugosari road in the district of Pasirian Lumajang district and the efficiency of time and cost of the project after the addition of the optimum workers in the improvement / widening project of Jalan Gondoruso - Jugosari, Pasirian District, Lumajang Regency. Analysis using regression analysis and crash program methods. Based on the results of the analysis concluded that the factors that influencefor delays in carrying out the work improvement / widening of Gondoruso - Jugosari Road, Pasirian District Lumajang Regency is a factor of the Work Environment and Materials / Materials and the result of acceleration using the crashing method with the addition of 14% of the workforce obtained an acceleration of 6 days from a total duration of 54 days for the work of Concrete Pavement Pavement with Single Reinforced Matting (Fs 45 cm thick 25 cm) to 48 days with a cost slope of Rp. 99,281,345,15.